2017
DOI: 10.3390/educsci7020054
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy amongst Health Professional University Students: A Study Using the Health Literacy Questionnaire

Abstract: Abstract:Background: This study aimed to assess and compare health literacy levels in a range of university-based health students. Methods: A survey containing the Health Literacy Questionnaire (HLQ) was administered to students enrolled in university-based medical, allied health or nursing degree programs. The HLQ scores and scale scores were compared across student groups. Results: In total, 374 students (24% response rate) with a median age of 25 years (range: 17-61 years), returned completed surveys. Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
76
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 44 publications
(35 reference statements)
5
76
0
5
Order By: Relevance
“…There is a requirement of improved health literacy training for all students acquiring healthcare degree as students must be prepared effectively for communicating with low health literacy patients in order to achieve maximum clinical outcomes. 7 The results of the present study are quite encouraging as they showed that majority of the undergraduate pharmacy students had adequate functional health literacy. The results of the current study highlighted that female students had relatively better functional health literacy as compared to male students.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…There is a requirement of improved health literacy training for all students acquiring healthcare degree as students must be prepared effectively for communicating with low health literacy patients in order to achieve maximum clinical outcomes. 7 The results of the present study are quite encouraging as they showed that majority of the undergraduate pharmacy students had adequate functional health literacy. The results of the current study highlighted that female students had relatively better functional health literacy as compared to male students.…”
Section: Discussionsupporting
confidence: 58%
“…Similar findings were reported from studies conducted in colleges and medical universities of China. [5][6][7][8] The results of the present study highlighted that students studying in the final professional had better functional health literacy than students studying in first and second professionals of Pharm.D. Similar findings were reported in studies conducted in Britain, Indonesia and china which concluded that health literacy scores were linked with year of study.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The health literacy of health profession students is of interest because improving health literacy of the general population is integral to being an efficient health professional [8]. Communication with consumers of health, providing health information to healthcare recipients, and delivering quality care are fundamental to students becoming work-ready health professionals by the time of graduation [3,[9][10][11]. The development of the Health Literacy Questionnaire (HLQ), has been shown to have excellent psychometric properties with high reliability and acceptability and has been used to explore health literacy across a range of populations world-wide [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The development of the Health Literacy Questionnaire (HLQ), has been shown to have excellent psychometric properties with high reliability and acceptability and has been used to explore health literacy across a range of populations world-wide [12][13][14]. The HLQ is designed to cover the extent of an individual's strengths and limitations of health literacy [9,10,15], with recent research demonstrating levels are varied [3, 9-11, 16, 17]. Zhang and colleagues [9,16] and Mullan and coworkers [10] reported that health literacy levels of health profession students is inadequate and requires targeted interventions to ensure they are work-ready at graduation.…”
Section: Introductionmentioning
confidence: 99%